The Split-Operator Technique for the Study of Spinorial Wave Packet Dynamics (Communications in Computational Physics, 2018)
The split-operator technique for wave packet propagation in quantum systemsis expanded here to the case of propagating wave functions describing Schrödingerparticles, namely, charge carriers in semiconductor nanostructures within the effectivemass approximation, in the presence of Zeeman effect, as well as of Rashba andDresselhaus spin-orbit interactions. We also demonstrate that simple modificationsto the expanded technique allow us to calculate the time evolution of wave packetsdescribing Dirac particles, which are relevant for the study of transport properties ingraphene.